Downregulation of miR‐106b induced breast cancer cell invasion and motility in association with overexpression of matrix metalloproteinase 2. Issue 1 (4th December 2013) - Ni, Xiaojian; Xia, Tiansong; Zhao, Yingchun; Zhou, Wenbin; Wu, Naping; Liu, Xiaoan; Ding, Qiang; Zha, Xiaoming; Sha, Jiahao; Wang, Shui
<x xml:space="preserve">Abstract</x> Breast cancer (BC) is one of the most common cancers in women, and it can often metastasize to the bone. The mechanism of BC bone metastasis remains unclear and requires in‐depth investigation. In a previous study, we found the expression of matrix metalloproteinase 2 (MMP2) to be significantly more pronounced at metastatic bone sites than at orthotopic sites. MicroRNA expression profiling showed miR‐106b to be markedly downregulated during BC bone metastasis. However, the specific manner in which MMP2 and miR‐106b are involved in the BC bone metastasis is still unclear. In the present study, we found MMP2 expression in orthotopic tumor tissue to be related to the risk of bone metastasis in BC patients. MiR‐106b levels in orthotopic tumor tissue showed a negative correlation with MMP2 expression and breast cancer bone metastasis. MMP2 was shown to be a direct target of miR‐106b. Both gain‐ and loss‐of‐function studies showed that MMP2 could promote the migration and invasion of BC cells and that miR‐106b could suppress both. The blockage of MMP2 by RNA interference mimicked the anti‐migration and anti‐invasion effects of miR‐106b, and introduction of MMP2 antagonized the function of miR‐106b. MMP2 was also found to regulate the ERK signaling cascade and so adjust the bone microenvironment to favor osteoclastogenesis and bone metastasis. These results suggest that MMP2 upregulation plays an important role in BC bone metastasis through ERK pathways, and miR‐106b directly regulates MMP2 expression. The miR‐106b/MMP2/ERK pathway may be a promising therapeutic target for inhibiting BC bone metastasis.